2019
DOI: 10.4012/dmj.2018-118
|View full text |Cite
|
Sign up to set email alerts
|

Improved osteoblast adhesion and osseointegration on TiO<sub>2</sub> nanotubes surface with hydroxyapatite coating

Abstract: To improve initial osteoblast adhesion and subsequent osseointegration, TiO2 nanotubes layer was constructed on the titanium (Ti) surface by anodic oxidation (AO), with an additional hydroxyapatite (HA) coating to form the AO/HA surface. Tests on in vitro cellular activity displayed that the AO surface, especially the AO/HA surface, promoted initial adhesion, proliferation and differentiation of osteoblast cells. The modified AO and AO/HA surfaces further presented an up-regulated gene expression of osteogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
(41 reference statements)
0
18
0
1
Order By: Relevance
“…We previously studied the cellular response and bone binding ability of the combination of TiO 2 nanotube surface with chemical component hydroxyapatite (HA). It was revealed that the nanotopography and HA coating played a synergistic role in promoting osteoblast adhesion, proliferation, differentiation, and osseointegration [17].…”
Section: Introductionmentioning
confidence: 99%
“…We previously studied the cellular response and bone binding ability of the combination of TiO 2 nanotube surface with chemical component hydroxyapatite (HA). It was revealed that the nanotopography and HA coating played a synergistic role in promoting osteoblast adhesion, proliferation, differentiation, and osseointegration [17].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that PSHA scaffolds are more capable of accelerating the maturation of osteogenic mineralization. Furthermore, with regard to OPN and OCN expression (markers of osteogenic differentiation at a late stage) ( Li et al, 2019 ). The expression of OPN and OCN in the PSHA group was significantly higher than in the EDHA group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the US substrate was successfully functionalized with hydroxyapatite coating (HApUS) and investigated for bioactivity. The combination of such specific nanotopography and bioactivity of HAp was previously reported to have a positive synergic effect on osseointegration in vivo [22]. Specifically, it was shown to upregulate the gene expressions of cell adhesion and osteogenic differentiation markers.…”
Section: Introductionmentioning
confidence: 93%